Pengaturan Dark Patterns Sebagai Tindak Pidana Dalam Hukum Perlindungan Konsumen di Indonesia - Risa Rifa’ul Azizah; Mochammad Tanzil Multazam (Indonesian Journal Publisher, 2025)
The development of digital technology has encouraged the use of interface design in electronic business activities including the practice of dark patterns which may influence consumer decision making through unbalanced information. This practice raises legal issues because it can reduce consumer rights to correct information and freedom of choice as regulated in Law Number 8 of 1999 on Consumer Protection. This study analyzes the regulation of dark patterns within consumer protection law and examines their potential classification as criminal acts based on the Consumer Protection Law the Criminal Code Law Number 1 of 2023 and the Law on Electronic Information and Transactions. This research uses a normative legal method with a statutory approach. The results show that although not explicitly regulated dark patterns may be classified as acts of business actors that violate legal obligations and cause harm to consumers and may fulfill criminal elements under certain conditions.